Histopathological characteristics of gynaecomastia in Southwestern Nigeria: A review from a tertiary hospital (2020)
Background: Gynaecomastia is a benign proliferation of the glandular tissue of the male breast. It is thought to be present in at least a third of men in the course of their lifetime. This study aims to review the histomorphological characteristics of gynaecomastia seen at the department of Pathology, University College Hospital (UCH), Ibadan, over 10 years period. Methods: A hospital-based retrospective study was undertaken to review the histopathology reports of all gynaecomastia cases diagnosed at the Department of Pathology, UCH Ibadan, over a 10‑year period from 01 January, 2009 to 31 December, 2018. Patient’s biodata, histological diagnosis and clinical details were extracted from the surgical day books and laboratory request forms. The data were analysed for the frequency distribution using the SPSS software version 22. Results: Gynaecomastia accounts for 2.5% of all breast biopsies received within the study period and accounted for 68.1% of all benign breast lesions seen in males. The left breast was the most affected with 48.8% of the cases, whereas 17.2% of the cases were bilateral. The age range of patients with gynaecomastia seen in this study is between 12 and 80 years with a mean age of 43.36 years. The most common histopathological subtype seen in this study is the florid type gynaecomastia. Conclusion: Gynaecomastia is the most common diagnosis from male breast biopsies. The left breast is the most commonly affected breast. The florid type gynaecomastia is the main histopathological variant seen in this study.